2023
DOI: 10.1007/s00068-023-02246-4
|View full text |Cite
|
Sign up to set email alerts
|

Time to surgery after proximal femur fracture in geriatric patients depends on hospital size and provided level of care: analysis of the Registry for Geriatric Trauma (ATR-DGU)

Abstract: Purpose Proximal femur fractures predominantly affect older patients and can mark a drastic turning point in their lives. To avoid complications and reduce mortality, expert associations recommend surgical treatment within 24–48 h after admission. Due to the high incidence, treatment is provided at a wide range of hospitals with different size and level of care, which may affect time to surgery. Methods Data from 19,712 patients included from 2016 to 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Optimization in patients care, especially prior to surgery may improve surgical outcome [ 14 ]. This is very demanding for some fractures, considering the guideline for the treatment of femoral neck fractures within 24 h in Germany [ 15 ]. However, studies have shown malnutrition in 73% of patients with hip fracture [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Optimization in patients care, especially prior to surgery may improve surgical outcome [ 14 ]. This is very demanding for some fractures, considering the guideline for the treatment of femoral neck fractures within 24 h in Germany [ 15 ]. However, studies have shown malnutrition in 73% of patients with hip fracture [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%